2012
DOI: 10.1590/s0365-05962012000200015
|View full text |Cite
|
Sign up to set email alerts
|

Association of giant congenital melanocytic nevus, halo nevus and vitiligo in a 75-year-old patient

Abstract: A giant congenital melanocytic nevus represents a rare condition. The halo phenomenon may be seen in congenital or acquired melanocytic nevi. In the literature, association of halo nevus and giant congenital melanocytic nevus is rare and the association of both with vitiligo even more rare. A 75-yearold woman at first consultation complained of a hyperchromic bluish-brown hairy macula on the lower back, buttocks and thighs present since birth and an achromic halo of onset three years ago. The histological feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Pers, 20 as indicated by Moss,70 found that 53.9% of his patients with GCMN had significant psychological and social difficulties as a result of their lesions. In another study of 29 children with GCMN, 71 social problems were 187,[190][191][192][193] Halo nevi: reports 191,194 Smooth muscle hamartoma: reports 195 Shokeir syndrome: 1 report 196 CMN, Congenital melanocytic nevi.…”
Section: Inheritance Key Pointmentioning
confidence: 99%
“…Pers, 20 as indicated by Moss,70 found that 53.9% of his patients with GCMN had significant psychological and social difficulties as a result of their lesions. In another study of 29 children with GCMN, 71 social problems were 187,[190][191][192][193] Halo nevi: reports 191,194 Smooth muscle hamartoma: reports 195 Shokeir syndrome: 1 report 196 CMN, Congenital melanocytic nevi.…”
Section: Inheritance Key Pointmentioning
confidence: 99%
“…1,4 Several cases of CMN have been reported in combination with vitiligo and/or halo formation around the congenital naevus (HN-CMN). 3,[5][6][7][8][9] In the majority of these cases a halo formation around the congenital naevus precedes the onset of vitiligo, while a reverse or simultaneous order of appearance has also been described. 10 The association between vitiligo and halo naevi (not including HN-CMN) is much better established.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“… 12 Most CMN cases with spontaneous regression and halo phenomenon are associated with development of vitiligo at a distant site. 4 6 , 11 Spontaneous regression of CMN without halo formation is a more exceptional case. 13 …”
Section: Discussionmentioning
confidence: 99%
“… 3 Spontaneous involution of CMN is a rare phenomenon, and it is often reported in association with halo phenomenon or vitiligo. 4 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation